Taxing the rich policy, evasion behavior, and portfolio choice: A sustainability perspective - Kuo-Shing Chen; Huolien Tsai (Cogent Business & Management, 2018)
In the spring of 2016, the tax-evasion revelations from the Panama Papers regarding the international clients of Mossack Fonseca shook the financial world. This article sheds light on whether taxing the rich will generate the tax-evasion effect, if the evasion behavior will affect the portfolio choice, and finally, the broader economic impacts of such tax evasion. The main insights are: (1) the evidence from the Panama Papers demonstrates that the supply of tax evasion services explains that evasion behavior rises steeply with wealth; (2) we also affirm that higher tax rates induce greater tax evasion activity and explain why the taxation system introduced by Hollande, which levied high tax on millionaires, failed in France; and (3) the primary components of billionaires' asset allocation involve adequately weighting long-term stock holdings. Finally, these findings provide some evidence on the sustainability of taxing the rich and the sustainable investing behavior of the ultra-wealthy.
Keywords: 650